2017
DOI: 10.1186/s12864-017-3726-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary physical or nutritional factors on morphology of rumen papillae and transcriptome changes in lactating dairy cows based on three different forage-based diets

Abstract: BackgroundRumen epithelial tissue plays an important role in nutrient absorption and rumen health. However, whether forage quality and particle size impact the rumen epithelial morphology is unclear. The current study was conducted to elucidate the effects of forage quality and forage particle size on rumen epithelial morphology and to identify potential underlying molecular mechanisms by analyzing the transcriptome of the rumen epithelium (RE). To achieve these objectives, 18 mid-lactation dairy cows were all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 71 publications
(88 reference statements)
1
44
0
1
Order By: Relevance
“…In our previous work, the cows in the RS group displayed a thicker ruminal papilla layer and epithelial layer than the cows in the CS group, which may prevent nutrient absorption and therefore affect the metabolite profile in the liver. Liver tissue metabolomics data had a clear discrimination between cows in the CS and RS groups.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In our previous work, the cows in the RS group displayed a thicker ruminal papilla layer and epithelial layer than the cows in the CS group, which may prevent nutrient absorption and therefore affect the metabolite profile in the liver. Liver tissue metabolomics data had a clear discrimination between cows in the CS and RS groups.…”
Section: Discussionmentioning
confidence: 89%
“…In our study, the nutrient composition was similar but the physical size showed great difference between the CS and RS diets. Both the proportion of particles with a size > 19 mm (40.4% vs 16.9%) and the peNDF >19 mm (14.9 vs 6.1) were significantly higher in the RS than CS, which increased the rumen epithelial thickness and inhibited the nutrient degradation and absorption, and thus limited the nutrient supplying and metabolism in the liver. Therefore, it is likely that different crop by‐products alter liver metabolism.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The outer dense plaque contains the intracellular ends of desmocollin and desmoglein; this last one being the structure, we were interested in analysing. Desmoglein ( DSG1 ) is a cell structure involved in cell‐to‐cell adhesion, and it is associated with cellular transport and structure through dynamic changes through ion bindings (Wang et al, ). DSG1 is highly expressed in stratified squamous epithelium, especially the stratum granulosum (Green & Simpson, ).…”
Section: Discussionmentioning
confidence: 99%